2021
DOI: 10.1002/adma.202007890
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Self‐Powered Integrated Sensing System with 3D Periodic Ordered Black Phosphorus@MXene Thin‐Films

Abstract: Accurate and continuous detection of physiological signals without the need for an external power supply is a key technology for realizing wearable electronics as next‐generation biomedical devices. Herein, it is shown that a MXene/black phosphorus (BP)‐based self‐powered smart sensor system can be designed by integrating a flexible pressure sensor with direct‐laser‐writing micro‐supercapacitors and solar cells. Using a layer‐by‐layer (LbL) self‐assembly process to form a periodic interleaving MXene/BP lamella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
141
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(152 citation statements)
references
References 48 publications
0
141
0
Order By: Relevance
“…Such enhancements are important to achieve allweather MSCs that deliver desired electrochemical performance. Incorporation of new materials into MXene-framework may also impart unique functions like pressure sensing 1324 and selfhealing 1325 which may not only reduce the footprint of integrated devices but also extend the usable life of such devices.…”
Section: D Materials For Micro-supercapacitorsmentioning
confidence: 99%
“…Such enhancements are important to achieve allweather MSCs that deliver desired electrochemical performance. Incorporation of new materials into MXene-framework may also impart unique functions like pressure sensing 1324 and selfhealing 1325 which may not only reduce the footprint of integrated devices but also extend the usable life of such devices.…”
Section: D Materials For Micro-supercapacitorsmentioning
confidence: 99%
“…[7] Among various type of actuators,photoactuator owns unique features of remote actuation, no contact, concise control, and abundant sources of light energy,which is suitable as driving unit for use in untethered soft robot. [8] Fort he purpose of fabricating high-performance photoactuator,i ti sc rucial to develop new light responsive materials.I nr ecent years,t wo dimensional (2D) nanomaterials such as graphene, [9] MXene [10] and MoS 2 [11] with unique structure and excellent optical properties have been used to prepare photoactuators with outstanding actuation performance,r evealing the great potential of the new 2D materials in the next-generation highperformance photoactuators.Black phosphorus (BP) is anew class of 2D nanomaterials with unique lamellar structure, excellent properties and promising applications in energy storage, [12] catalysis, [13] sensing, [14] and biomedicine. [15] In particular,B Ph as shown anisotropic mechanical property, [16] exceptional electromechanical performance, [17] outstanding photothermal conversion capability across ab road range of wavelengths, [18] and thermal expansion feature, [19] making it ideal candidate for the fabrication of soft actuators.F or example,W ue tal.,f abricated black phosphorus based electrochemical actuator with high actuation properties, which mainly stems from the ordered lamellar structure and large redox activity of the black phosphorus for ions with smooth diffusion and flooding accommodation.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] Among these materials, Gogotsi et al in 2011 reported 2D MXene nanosheets based on transition metal carbide and nitride materials. [21] These materials have been extensively studied for numerous applications that include sensors, [22][23][24] light-emitting diodes, [25][26][27] energy storage, [28][29][30][31][32][33][34] water purification, [35][36][37][38] K. Rasool Qatar Environment and Energy Research Institute Hamad Bin Khalifa University (HBKU) Qatar Foundation 34110, Doha Qatar F. Mateen Department of Chemical and Biochemical Engineering Dongguk University Seoul 04620, Republic of Korea supercapacitors, [39][40][41][42] photocatalysis, [43][44][45][46] biomedical, [47][48][49][50][51][52] and electromagnetic [52][53][54][55] applications. MXenes are a unique and unusual combination of early transition metal carbide/nitrides or carbonitrides that are typically synthesized by a top-down sele...…”
Section: Introductionmentioning
confidence: 99%